2009
DOI: 10.1007/s12041-009-0032-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of combined genomic variants in a Jordanian family with familial non-autoimmune hyperthyroidism

Abstract: Five patients, four brothers and their paternal aunt, presented with a history of overt hyperthyroidism and goiter. Hyperthyroidism in this family was remarkable for its poor response to carbimazole (30-50 mg/d). The thyroid ultrasound showed a diffusely enlarged gland in all the affected members, and thyroid stimulating antibodies (TSAB) were negative. Screening for germline mutations in thyroid stimulating hormone (TSH) receptor (TSHR) gene was performed by direct sequencing of genomic DNA extracted from per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The same SNPs were identified in two family members: the father was heterozygous for the TSHR polymorphism but wild type for Gsa, while the mother was heterozygous for the Gsa polymorphism and wild type for the TSHR variant. Of interest, the TSHR SNP was found to be associated with familial nonautoimmune hyperthyroidism, as well as with AFTNs (32,33). To the best of our knowledge, no other data are available in the literature about the prevalence of each of the two SNPs in AFTNs as well as in the general population.…”
mentioning
confidence: 99%
“…The same SNPs were identified in two family members: the father was heterozygous for the TSHR polymorphism but wild type for Gsa, while the mother was heterozygous for the Gsa polymorphism and wild type for the TSHR variant. Of interest, the TSHR SNP was found to be associated with familial nonautoimmune hyperthyroidism, as well as with AFTNs (32,33). To the best of our knowledge, no other data are available in the literature about the prevalence of each of the two SNPs in AFTNs as well as in the general population.…”
mentioning
confidence: 99%
“… 18 , 19 In Jordan, a study conducted in 2009 by Ismail et al reported on the detection of combined genomic variants in families with hyperthyroidism. 20 …”
Section: Discussionmentioning
confidence: 99%